2013
DOI: 10.1088/0957-4484/24/44/444006
|View full text |Cite
|
Sign up to set email alerts
|

Development of 3D carbon nanotube interdigitated finger electrodes on polymer substrate for flexible capacitive sensor application

Abstract: This study reports a novel approach to the implementation of 3D carbon nanotube (CNT) interdigitated finger electrodes on flexible polymer, and the detection of strain, bending curvature, tactile force and proximity distance are demonstrated. The merits of the presented CNT-based flexible sensor are as follows: (1) the silicon substrate is patterned to enable the formation of 3D vertically aligned CNTs on the substrate surface; (2) polymer molding on the silicon substrate with 3D CNTs is further employed to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Though these sensor materials generally are based on many mechanisms such as electromagnetic induction, infrared emission, ultrasonic wave detection etc., capacitance or resistance measurements still offer an easier way. Using this principle, several polymers and their nanocomposites have been assimilated in touch screens, media players, and satellite‐navigation systems as short‐range proximity sensors . However, eco‐friendly, transparent, non‐metallic, and low‐cost sensor materials of reduced size that would be useful in various electronic fields are still under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Though these sensor materials generally are based on many mechanisms such as electromagnetic induction, infrared emission, ultrasonic wave detection etc., capacitance or resistance measurements still offer an easier way. Using this principle, several polymers and their nanocomposites have been assimilated in touch screens, media players, and satellite‐navigation systems as short‐range proximity sensors . However, eco‐friendly, transparent, non‐metallic, and low‐cost sensor materials of reduced size that would be useful in various electronic fields are still under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there could be failures resulting from the occurrences of division and delamination because sometimes the metal is not strongly adhesive to polymer and the thin film process could also pose limitations on the height of electrode. In order to solve this problem, Fang and co‐workers come up with a brief molding process, which serves for the purpose of achieving a capacitive flexible sensor with 3D CNT interdigitated finger electrodes . According to their research, further improvement in the design of the silicon mold was made, which was to combine CNT interdigitated electrodes with 3D polymer diaphragms and supporters.…”
Section: Wearable Sensor Applicationsmentioning
confidence: 99%
“…Hence, the performance of the exible resistive pressure sensor could be improved by adjusting the feature of microstructures or through the introduction of smart 3-D microstructures. 3,4,13,14,[27][28][29] Soonjae et al fabricated a piezoresistive CNT-polymer-composite-based tactile sensor, and observed a sensitivity of 6.67%/N for the maximum force up to 2 N. 27 Yilmazoglu et al studied a structure that integrated exible, vertically aligned MWCNT arrays between at carbon nanotube electrodes. Due to the exible structure of the microsized 3D aligned CNTs, good piezoresistivity with decrease of resistance up to $35% at 32 mN of the MWCNT arrays was observed.…”
Section: Introductionmentioning
confidence: 99%